Optimization of high-performance liquid chromatographic parameters for the determination of capsaicinoid compounds using the simplex method - Karnka R. (2014)
A high-performance liquid chromatographic method was developed for the analysis of capsaicinoid compounds, the pungent principles of capsicum fruits. A sequential simplex method was applied to optimize the chromatographic response function used to assess the quality of separation by varying the chromatographic parameters. The separation was achieved in 11 min using a C-8 column of 15-cm length and 4.6 mm diameter using a UV detector. A flow rate of 1.15 ml min-1 at a column temperature of 43.5°C using 63.7% methanol in water gave the most efficient separation. The method was found to be suitable for the determination of the major capsaicinoid compounds in the capsicum samples.